White-on-Black Painted Ware. A Case Study for the Relationship between Artifact Groups and Historical В vents - Nicol, Murray Boyd
Ph. D.; Supervisors: M. Greenberg and R. H. Dyson, Jr.; Obtainable from University Microfilms Inc., Ann Arbor, Mich. (Order No. 66-4635. Microfilm $6.50; Xerography $23.20); Dissertation Abstracts 26/12.I (Ann Arbor, Mich., June 1966) 7273; not: Hurrians; the origin of the WB painted ware should probably be sought in the Coastal Plain north of Beirut as well as in the Aegean Islands.